Electrochemical biosensor for cancer cell detection based on a surface 3D micro-array. Issue 2 (20th December 2017) - An, Li; Wang, Guangtong; Han, Yu; Li, Tianchan; Jin, Peng; Liu, Shaoqin
Abstract : We have developed an efficient strategy to capture, detect and release CTCs from the blood of cancer patients using a benzoboric acid modified gold-plated polymeric substrate with a regular 3D surface array. Abstract : The detection of rare circulating tumour cells (CTCs) in patients' blood is crucial for the early diagnosis of cancer, highly precise cancer therapy and monitoring therapeutic outcomes in real time. In this study we have developed an efficient strategy to capture and detect CTCs from the blood of cancer patients using a benzoboric acid modified gold-plated polymeric substrate with a regular 3D surface array. Compared with the smooth substrate, the substrate with the surface 3D microarrays exhibited a higher capture efficiency, i.e. 3.8 times that afforded by the smooth substrate. Additionally, due to the reversible reaction between the benzoboric acid on the 3D microarray and the sialic acid on CTCs, our strategy allowed for easy detachment of the captured CTCs from the substrate without causing critical damage to the cells. This will be of benefit for gaining further access to these rare cells for downstream characterization. The proposed strategy provides several advantages, including enhanced capture efficiency, high sensitivity, low cost and recovery of isolated CTCs, and could become a promising platform for early stage diagnosis of cancer.